2021
DOI: 10.1371/journal.pone.0247812
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of violence and mental health outcomes among Asian American transgender adults in the United States

Abstract: Purpose We addressed prevalence and factors associated with mental health outcomes (suicidal behavior and psychological distress) among Asian Americans (AA), who identify as transgender, a key group among sexual and gender minorities that is overlooked and understudied. Methods We used data from 2015 United States Transgender Survey during 2019–2020 with our population as census defined AA. Outcomes included suicidal ideation, suicidal thoughts, and serious psychological distress (SPD). Independent variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…All mental health variables were assessed using one-item questions except for the 10-item Kessler Psychological Distress (K10) Scale. The K10 demonstrated high internal consistency in the overall sample, and we used this scale to identify if participants had low or moderate (0-11), high (12)(13)(14)(15)(16)(17)(18)(19), or very high ( ‡ 20) psychological distress. 27 Participants were asked about their experiences accessing gender-affirming care and general health services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mental health variables were assessed using one-item questions except for the 10-item Kessler Psychological Distress (K10) Scale. The K10 demonstrated high internal consistency in the overall sample, and we used this scale to identify if participants had low or moderate (0-11), high (12)(13)(14)(15)(16)(17)(18)(19), or very high ( ‡ 20) psychological distress. 27 Participants were asked about their experiences accessing gender-affirming care and general health services.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Moreover, existing (limited) studies that have looked at mental health differences across ethnic/racial groups of transgender people often housed Asian within the broader ethnic minority groups, 14,15 except for one recent U.S. study that explored the relationships between violence exposures and mental health outcomes for Asian transgender people. 16 While research on transgender people in Asia is beginning to flourish, 9,17,18 there needs to be careful consideration when extrapolating these findings to Asian transgender people in Western countries such as Aotearoa/New Zealand which have unique migration contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Violence against trans persons of color is particularly high; the HRC report noted that fatal violence disproportionately affected Black trans women. Becerra et al, reported that a majority of their study population of Asian-American transgender persons reported experiencing any form of abuse/violence (66.9%), 52.4% reported abuse/violence from romantic/sexual partner (52.4%), and 29.5% reported harassment/abuse when trying to use a bathroom [36].…”
Section: Discussionmentioning
confidence: 99%
“…First, few studies use longitudinal data (e.g., tracking substance use from adolescence into emerging adulthood, when substance use typically peaks [ 14 , 15 , 16 ]). Second, few studies with disaggregated SGM samples have included Asian American and Pacific Islander SGM populations, who tend to be underrepresented in SGM research more generally [ 17 , 18 ]. Another gap in the extant literature relates to limited understanding of how substance use may differentially affect multiple domains of outcomes across SGM individuals with different racial/ethnic identities.…”
Section: Introductionmentioning
confidence: 99%